2020
DOI: 10.1177/0363546520905543
|View full text |Cite
|
Sign up to set email alerts
|

What Can a Jump Tell Us About Elbow Injuries in Professional Baseball Pitchers?

Abstract: Background: The incidence rate of elbow injuries has been rising in recent years among professional baseball pitchers. Determining valid screening procedures that allow practitioners to identify pitchers at an increased risk of such injuries is therefore of critical importance. Purpose: To validate the use of countermovement jump (CMJ) tests as a diagnostic tool for pitcher conditioning. Study Design: Case-control study; Level of evidence, 3. Methods: More than 500 pitchers at a single professional baseball or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…With the results of the present study, the authors suggest that baseball pitchers who are observed to have greater DHRT and a lower self-reported starting pitching age undergo further screening for other known modifiable risk factors associated with the risk of elbow injury. Numerous studies have identified potential modifiable risk factors for throwing-related elbow injury, including, but not limited to the following: shoulder total range of motion loss and shoulder external rotation loss, 11 the use of self-reported questionnaires to identify potential overuse parameters, 24 kinetic chain deficits, 10,13,16 glenohumeral shoulder abduction difference, 34 deficits in rotator cuff strength, 12 and performance-based parameters during the throwing motion. 2,3,8,25,30,31 These factors can be readily screened for, and implementation of an injury risk reduction program to improve observed deficits may help minimize the risk of UCL injury in these baseball pitchers.…”
Section: Discussionmentioning
confidence: 99%
“…With the results of the present study, the authors suggest that baseball pitchers who are observed to have greater DHRT and a lower self-reported starting pitching age undergo further screening for other known modifiable risk factors associated with the risk of elbow injury. Numerous studies have identified potential modifiable risk factors for throwing-related elbow injury, including, but not limited to the following: shoulder total range of motion loss and shoulder external rotation loss, 11 the use of self-reported questionnaires to identify potential overuse parameters, 24 kinetic chain deficits, 10,13,16 glenohumeral shoulder abduction difference, 34 deficits in rotator cuff strength, 12 and performance-based parameters during the throwing motion. 2,3,8,25,30,31 These factors can be readily screened for, and implementation of an injury risk reduction program to improve observed deficits may help minimize the risk of UCL injury in these baseball pitchers.…”
Section: Discussionmentioning
confidence: 99%
“…Kraska et al [ 51 ] demonstrated that when athletes perform a series of vertical jumps across a spectrum of loads that weak athletes, even slightly loaded (20 kg, an empty barbell), “drop off” a substantial amount (e.g., peak power output drops >30% between from unloaded and loaded 20 kg condition). Indeed, weaker athletes are at greater risk of experiencing non-contact injuries due to the inability to withstand eccentric braking forces during high velocity change of direction movement tasks [ 28 , 52 , 56 , 57 , 58 ]. This risk is increased when the athlete is heavily fatigued [ 59 , 60 , 61 ].…”
Section: Phasesmentioning
confidence: 99%
“…Compared with the traditional pneumatic actuator, it has the advantages of simple structure, large output force-to-weight ratio, high energy conversion efficiency, and good bionic performance. We use it as the driver of the human-like robotic arm to reduce the cost and improve the flexibility of the mechanism [ 1 ]. At present, the structure of pneumatic muscle bionic manipulators is continuously researched and developed at home and abroad, and many eye-catching results have been obtained.…”
Section: Introductionmentioning
confidence: 99%